Texture analysis in perfusion images of prostate cancer - a case study - Śmietański, Jacek; Tadeusiewicz, Ryszard (1947- ); Łuczyńska, Elżbieta (Zielona Góra: Uniwersytet Zielonogórski)
The analysis of prostate images is one of the most complex tasks in medical images interpretation. It is sometimes very difficult to detect early prostate cancer using currently available diagnostic methods. But the examination based on perfusion computed tomography (p-CT) may avoid such problems even in particularly difficult cases. However, the lack of computational methods useful in the interpretation of perfusion prostate images makes it unreliable because the diagnosis depends mainly on the doctor?s individual opinion and experience. In this paper some methods of automatic analysis of prostate perfusion tomographic images are presented and discussed
Keywords: prostate cancer; perfusion computed tomography; medical image analysis; pattern recognition